2017
DOI: 10.1111/1440-1681.12661
|View full text |Cite
|
Sign up to set email alerts
|

Renal simplicity denervation reduces blood pressure and renal injuries in an obesity‐induced hypertension dog model

Abstract: This study aimed to investigate the effects of renal sympathetic denervation (RDN) on blood pressure, renal function, and renal tissue pathological changes in obesity-induced hypertensive dogs. Thirty-two beagle dogs (10-12 months) were randomized to the control (n=10) and model groups (n=22). High-fat diet (HFD) was used to establish the obesity-induced hypertensive model. After 3 months of HFD, 20 animals with successfully induced hypertension were randomized to the RDN (n=10) and sham groups (n=10). Renal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…This phenomenon is exacerbated in the presence of AAC and aortic stiffening, which induce the transmission of abnormally high pulsatile stresses in renal microvessels . In this pathophysiological context, the maintenance of eGFR despite a large decrease in BP suggests that the addition of RDN to SSAHT including a renin–angiotensin system blocker and a calcium channel blocker (acting on postglomerular and both pre‐and postglomerular resistances, respectively) may have induced specific and subtle renal hemodynamic changes detectable only in the patients with the lowest AAC burden, as expected from experimental models . A small cohort study reported an increase in renal artery mean flow 6 months after RDN, as assessed by 3‐dimensional magnetic resonance angiography .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This phenomenon is exacerbated in the presence of AAC and aortic stiffening, which induce the transmission of abnormally high pulsatile stresses in renal microvessels . In this pathophysiological context, the maintenance of eGFR despite a large decrease in BP suggests that the addition of RDN to SSAHT including a renin–angiotensin system blocker and a calcium channel blocker (acting on postglomerular and both pre‐and postglomerular resistances, respectively) may have induced specific and subtle renal hemodynamic changes detectable only in the patients with the lowest AAC burden, as expected from experimental models . A small cohort study reported an increase in renal artery mean flow 6 months after RDN, as assessed by 3‐dimensional magnetic resonance angiography .…”
Section: Discussionmentioning
confidence: 91%
“…25,26 In this pathophysiological context, the maintenance of eGFR despite a large decrease in BP suggests that the addition of RDN to SSAHT including a reninangiotensin system blocker and a calcium channel blocker (acting on postglomerular and both pre-and postglomerular resistances, 27 respectively) may have induced specific and subtle renal hemodynamic changes detectable only in the patients with the lowest AAC burden, as expected from experimental models. 28,29 A small cohort study reported an increase in renal artery mean flow 6 months after RDN, as assessed by 3-dimensional magnetic resonance angiography. 30 In addition, renal vascular resistance has been shown to decrease 3 to 6 months after RDN in patients with resistant hypertension, 31,32 with no significant increase in renal perfusion detectable on MRI 33 or improvement in renal oxygenation, as determined by blood oxygen level-dependent MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, absolute dietary fat intake increased with food intake in the weight-change group. However, the diet was the same for both groups and thus the macronutrient ratio remained the same and was not extreme compared to other studies [16][17][18]. Furthermore, increased cardiac output in obesity is more strongly correlated with fat-free body mass than with fat mass [46].…”
Section: Plos Onementioning
confidence: 92%
“…In the canine model of obesity-induced hypertension, 10% weight-gain increases heart rate, cardiac output, and blood pressure [44]. However, weight-gain is often induced by feeding a high amount of fat in canine models of obesity [16][17][18]. In fact, dogs already show increased heart rate on the first day of a diet supplemented with beef fat [45].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation